Personality traits of the alternative DSM-5 model and the attachment dimensions in Portuguese adults - Rosa-Mendes, M.; Pires, R.; Sousa Ferreira, A. (Personality and Individual Differences, 2019)
Attachment experiences have been acknowledged as playing a fundamental role in personality functioning and psychopathology development across the lifespan. Although previous research has examined the associations between attachment styles/dimensions and personality traits, it has not focused on the maladaptive personality traits included in Section III of the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5). The current study aimed to explore the associations and gender differences between the maladaptive personality traits of the Alternative DSM-5 Model for Personality Disorders and the two dimensions of adult attachment style (Anxiety and Avoidance). A socio-demographic questionnaire and the Portuguese adaptations of the Personality Inventory for the DSM-5 (PID-5) and the Experiences in Close Relationships (ECR) were applied to 106 Portuguese adults in a nonclinical sample. Gender differences in some personality traits, but not in the attachment dimensions, were found. Negative Affectivity particularly associated with Attachment Anxiety and Detachment especially correlated with Attachment Avoidance for both males and females. Attachment Anxiety and Avoidance were also found to account for less than half of the variance in all DSM-5 domains. These results appear to reinforce that attachment is closely related to personality and psychopathology. Limitations, future directions and clinical implications are discussed.